Contested Discursive Framing of a Bank’s Cooptative Joint CSR Model - Galia, Riki (Qualitative Sociology Review, 2023)
There is a dearth of critical ethnographic research that focuses on the semiotic-discursive features of corporate social responsibility (CSR) framing in business and nonprofit (BUS-NPO) partnerships. This article contributes to CSR scholarship by combining ethnographic methods (participant observation, in-depth interviews, and textual materials) and semiotic analysis to demonstrate how a bank-NPO partnership is discursively framed in the context of agonistic interactions and its implications in terms of cooptation. This article crystallizes two arguments. First, the bank’s joint CSR initiatives represent a discursively framed and validated model of CSR as a commodity aiming at advancing bank interests at the cost of avoiding substantive and sustained social responsibility. Second, the joint CSR model, discursively framed as a cooptative partnership discourse, is effectively realized through the practices of the cooptative relationship between the bank and the NPOs.